HAILEY-HAILEY DISEASE – A CASE REPORT - P NAIR, ANJALY; JOSEPH, SIBY; R, LAKSHMI; KURIAN, SUNU (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Hailey-Hailey disease (HHD) is a rare autosomal dominant skin condition discovered in 1939 by Hailey brothers. Prevalence is found to be around 1 in 50,000 and is relatively uncommon in India. First onset of disease occurs between 20 to 40 years of age, usually presented in the 3rd and 4th decades of life. Here, we report a case of a 50-year-old female who presented with clinical features of the HHD and showed greater response to the treatment.